Antioxidant activity, determination of total phenolic and flavonoid content of Muntingia calabura L. Extracts - Anita Dwi Puspitasari; Ririn Lispita Wulandari (Pharmaciana, 2017)
Muntingia calabura L. leaves were contained alkaloids, saponins, phenolic, flavonoids, and tannin. Phenolic and flavonoids compound had antioxidant activity. The present study aims to determine the antioxidant activity, determination of total phenolic and flavonoid content of ethanol extract of Muntingia calabura L. leaves and its fractions. Muntingia calabura L. leaves were macerated with 96% ethanol and then evaporated until ethanol extract was obtained. The ethanol extract was dissolved into water and then partitioned with n hexane and ethyl acetate to obtain the n hexane fraction, ethyl acetate fraction and water fraction. Determination of antioxidant activity of extracts and fractions was performed by free radical capture measurement method by 1,1-diphenyl-2-picrylhydrazyl (DPPH) in vitro. Vitamin C was used as a positive control with IC50 value of        25.74 µg/mL. The total phenolic and flavonoid content were determined using the colorimetric method using standard gallic acid for total phenolics and standard quercetin for flavonoid content. The results showed that ethyl acetat fraction showed the highest antioxidant activity with IC50 79.37 μg/mL value compared to n hexane fraction (101.36 μg/mL), ethanol extract (126.47 μg/mL), and water fraction (129.85 μg/mL). The ethyl acetate fraction contains the highest total phenolic of 510.57 mg GAE/g extract compared to ethanol extract (311.10 mg GAE/g extract), water fraction (292.74 mg GAE/g) extract, and n hexane fraction (103.95 mg GAE/g extract). The ethyl acetate fraction contained the highest flavonoid content of 76.32 mg QE/g extract compared to ethanol extract (39.63 mg QE/g extract), water fraction (14.29 mg QE/g extract) and n hexane fraction (3.30 mg QE/g extract). Total phenolic and total flavonoid levels were positively correlated with antioxidant activity